2015
DOI: 10.1186/s12910-015-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

Can UK NHS research ethics committees effectively monitor publication and outcome reporting bias?

Abstract: BackgroundPublication and outcome reporting bias is often caused by researchers selectively choosing which scientific results and outcomes to publish. This behaviour is ethically significant as it distorts the literature used for future scientific or clinical decision-making. This study investigates the practicalities of using ethics applications submitted to a UK National Health Service (NHS) research ethics committee to monitor both types of reporting bias.MethodsAs part of an internal audit we accessed rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…9 There have been calls for audits of access to trial results for performance monitoring and comparison, 8 with several recent examples including trials from individual research centres, [10][11][12] all drugs approved in one year, 13 and all trials approved by individual ethics committees. 14 No attempts have, however, been made to systematically compare funder or sponsor policies on transparency. doi: 10.1136/bmj.j3334 | BMJ 2017;358:j3334 | the bmj We identified pharmaceutical companies' policies on access to information about clinical trials and extracted structured data characterising their commitments to register clinical trials, share summary results, share CSRs, and give access to trial data for current and past trials (box 1); and we assessed concordance with ethical and professional guidance.…”
Section: Introductionmentioning
confidence: 99%
“…9 There have been calls for audits of access to trial results for performance monitoring and comparison, 8 with several recent examples including trials from individual research centres, [10][11][12] all drugs approved in one year, 13 and all trials approved by individual ethics committees. 14 No attempts have, however, been made to systematically compare funder or sponsor policies on transparency. doi: 10.1136/bmj.j3334 | BMJ 2017;358:j3334 | the bmj We identified pharmaceutical companies' policies on access to information about clinical trials and extracted structured data characterising their commitments to register clinical trials, share summary results, share CSRs, and give access to trial data for current and past trials (box 1); and we assessed concordance with ethical and professional guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research looking at publication rates of projects reviewed by HRA RECs indicated that most projects take at least 4 years before a resulting publication in a peer-reviewed journal is produced. 7 It might also be expected that the older a research database is the more likely it will be for other researchers to know about it and thus make a data access request. Here, the number of research databases approved per year is shown in figure 4 , although it should be noted that some databases may have been in operation prior to the HRA application date.…”
Section: Resultsmentioning
confidence: 99%
“…This request formed part of the wider 'transparency agenda' being pursued as a statutory duty by the HRA, but further encouraged by organisations such as the AllTrials campaign 5 and the REWARD Alliance. 6 A previous audit by the HRA showed that only one-third of regular projects reviewed by RECs publish their results, 7 raising a subsequent concern that research database projects may also be underperforming in terms of publishing outputs.…”
Section: Open Accessmentioning
confidence: 99%
“…10 By cross referencing initial applications with data in clinical trial registries and publication databases, the pilot was able to determine whether projects had published in the scientific literature (32%, 37/116, had) and whether researchers reported their originally stated outcomes (only 43%, 12/28, had).…”
Section: Lack Of Coordinationmentioning
confidence: 99%